Student Satisfaction and Learning Outcomes for the Pediatric Nursing Course Through Project Based Learning - Fitriana Noor Khayati; Setianingsih Setianingsih (Indonesian Journal of Global Health Research, 2023)
Educational institutions organize education to prepare students to have knowledge, attitudes, and psychomotor skills. The learning process is organized to achieve Graduate Learning Outcomes which refers to the Indonesia's national qualifications framework. The learning process is interactive, holistic, integrative, scientific, contextual, thematic, effective, collaborative and student-centered. Therefore it is necessary to choose a learning strategy that is in accordance with the learning achievements of graduates. Objective: This study aims to determine student satisfaction and learning outcomes in the Pediatric Nursing Course through Project Based Learning (PjBL). Method: This research design is a type of quantitative descriptive research. The population in this study were students from Diploma Nursing Program in Universitas Muhammadiyah Klaten. The population of this study was 350 students, while the research participants were 107 students. The participants were students from Diploma Nursing Program who are currently taking Pediatric Nursing courses. Sampling technique was total sampling. Data collection used a questionnaire designed by the researcher. The data were then analyzed using univariate analysis. Results: Most of them got learning outcomes A, namely as many as 51 people (47.7%) and student satisfaction was mostly very satisfied, namely as many as 90 people or 84.1%. Conclusions: After participating in PjBL activities, student learning outcomes were very good and student satisfaction was very satisfied.